Diet–Microbiota Interactions Alter Mosquito Development - Martinson, Vincent G.; Strand, Michael R. (Frontiers in Microbiology, 2021)
Gut microbes and diet can both strongly affect the biology of multicellular animals, but it is often difficult to disentangle microbiota-diet interactions due to the complex microbial communities many animals harbor and the nutritionally-variable diets they consume. While theoretical and empirical studies indicate that greater microbiota diversity is beneficial for many animal hosts, there have been few tests performed in aquatic invertebrates. Most mosquito species are aquatic detritivores during their juvenile stages that harbor variable microbiotas and consume diets that range from nutrient-rich to nutrient-poor. In this study, we produced a gnotobiotic model that allowed us to examine how interactions between specific gut microbes and diets affect the fitness of Aedes aegypti, the yellow fever mosquito. Utilizing a simplified 7-member community of bacteria (ALL7) and various laboratory and natural mosquito diets, we allowed larval mosquitoes to develop under different microbial and dietary conditions and measured the resulting time to adulthood and adult size. Larvae inoculated with the ALL7 or a more complex community developed similarly when fed nutrient-rich rat chow or fish food laboratory diets; whereas, larvae inoculated with individual bacterial members of the ALL7 community exhibited few differences in development when fed a rat chow diet but exhibited large differences in performance when fed a fish food diet. In contrast, the ALL7 community largely failed to support the growth of larvae fed field-collected detritus diets unless supplemented with additional protein or yeast. Collectively, our results indicate that mosquito development and fitness are strongly contingent on both diet and microbial community composition.